Sbk2, a Newly Discovered Atrium-Enriched Regulator of Sarcomere Integrity. Issue 1 (19th May 2022) - van Gorp, Pim R.R.; Zhang, Juan; Liu, Jia; Tsonaka, Roula; Mei, Hailiang; Dekker, Sven O.; Bart, Cindy I.; De Coster, Tim; Post, Harm; Heck, Albert J.R.; Schalij, Martin J.; Atsma, Douwe E.; et al.
Abstract : Background: Heart development relies on tight spatiotemporal control of cardiac gene expression. Genes involved in this intricate process have been identified using animals and pluripotent stem cell-based models of cardio(myo)genesis. Recently, the repertoire of cardiomyocyte differentiation models has been expanded with iAM-1, a monoclonal line of conditionally immortalized neonatal rat atrial myocytes (NRAMs), which allows toggling between proliferative and differentiated (ie, excitable and contractile) phenotypes in a synchronized and homogenous manner. Methods: In this study, the unique properties of conditionally immortalized NRAMs (iAMs) were exploited to identify and characterize (lowly expressed) genes with an as-of-yet uncharacterized role in cardiomyocyte differentiation. Results: Transcriptome analysis of iAM-1 cells at different stages during one cycle of differentiation and subsequent dedifferentiation identified ≈13 000 transcripts, of which the dynamic changes in expression upon cardiomyogenic differentiation mostly opposed those during dedifferentiation. Among the genes whose expression increased during differentiation and decreased during dedifferentiation were many with known (lineage-specific) functions in cardiac muscle formation. Filtering for cardiac-enriched low-abundance transcripts, identified multiple genes with an uncharacterized role during cardio(myo)genesis including Sbk2 (SH3 domain binding kinase family member 2). Sbk2 encodes an evolutionarily conserved putative serine/threonine protein kinase, whose expression is strongly up- and downregulated during iAM-1 cell differentiation and dedifferentiation, respectively. In neonatal and adult rats, the protein is muscle-specific, highly atrium-enriched, and localized around the A-band of cardiac sarcomeres. Knockdown of Sbk2 expression caused loss of sarcomeric organization in NRAMs, iAMs and their human counterparts, consistent with a decrease in sarcomeric gene expression as evinced by transcriptome and proteome analyses. Interestingly, co-immunoprecipitation using Sbk2 as bait identified possible interaction partners with diverse cellular functions (translation, intracellular trafficking, cytoskeletal organization, chromatin modification, sarcomere formation). Conclusions: iAM-1 cells are a relevant and suitable model to identify (lowly expressed) genes with a hitherto unidentified role in cardiomyocyte differentiation as exemplified by Sbk2: a regulator of atrial sarcomerogenesis.